Harnessing foreign direct investment for local development? Spillovers in apparel global value chains in sub-Saharan Africa - Cornelia Staritz; Stacey Frederick (Austrian Foundation for Development Research (ÖFSE), 2016)
At the beginning of the 2000s, the introduction of the African Growth and Opportunity Act (AGOA) combined with Multi-Fibre Arrangement (MFA) quotas contributed to a boom in foreign direct investment (FDI) in the Sub-Saharan African (SSA) apparel industry, leading to a major growth in exports and jobs. Beyond this, the possibility of exploiting the spillover potential of this FDI raised significant hopes of developing a locally-embedded SSA apparel export industry. The paper explores the level and nature of FDI spillovers and the factors supporting and constraining them focusing on three of the leading SSA apparel exporter countries - Kenya, Lesotho, and Swaziland. We find that despite significant investments to attract FDI, virtually no locally-owned apparel firms are exporting or subcontracting, local value added remains low, local participation in management is limited, and domestic suppliers are almost absent in core and even most non-core inputs. In addition to domestic absorption capacity, the potential for and the nature of FDI spillovers is determined by the strategy of foreign investors and the governance of global value chains (GVCs). We find across all countries FDI strategies that severely limit spillover potential, including a concentration in low value added activities, external control of sourcing, and reliance on expatriates in managerial and technical positions. This is aggravated by a weak domestic absorptive capacity through weak skills development, barriers in the domestic business climate, ineffective policies to support local small and medium enterprises, and a missing local.
Keywords: 330; foreign direct investment; spillovers; global value chains; apparel; Sub-Saharan Africa